2013
DOI: 10.1111/1471-0528.12285
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects in a national cohort of pregnant women with HIV infection in Italy, 2001–2011

Abstract: Objective We used data from a national study of pregnant women with HIV to evaluate the prevalence of congenital abnormalities in newborns from women with HIV infection.Design Observational study.Setting University and hospital clinics.Population Pregnant women with HIV exposed to antiretroviral treatment at any time during pregnancy.Methods The total prevalence of birth defects was assessed on live births, stillbirths, and elective terminations for fetal anomaly. The associations between potentially predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
(37 reference statements)
2
24
1
Order By: Relevance
“…We observed an overall prevalence of 6.78 CAs for every 100 live births, which is considerably higher than many prior studies of HIV-exposed infants in the U.S. and the U.K, with reported prevalences ranging from 2.8% to 5.5% 47, 12,13 and higher than the rate of 3.2% in a recent Italian cohort, 10 but is similar to the 6.2% rate reported by a Latin American study. 27 We observed an increasing trend in the rate of CAs from prior to 2002 through 2010, followed by a slight decline through 2012.…”
Section: Discussioncontrasting
confidence: 73%
“…We observed an overall prevalence of 6.78 CAs for every 100 live births, which is considerably higher than many prior studies of HIV-exposed infants in the U.S. and the U.K, with reported prevalences ranging from 2.8% to 5.5% 47, 12,13 and higher than the rate of 3.2% in a recent Italian cohort, 10 but is similar to the 6.2% rate reported by a Latin American study. 27 We observed an increasing trend in the rate of CAs from prior to 2002 through 2010, followed by a slight decline through 2012.…”
Section: Discussioncontrasting
confidence: 73%
“…Twenty-six publications reported HBV infection prevalence [63, 65, 69, 71, 79-81, 89, 102, 106, 110, 123, 141, 144, 147, 150, 151, 154, 157, 159, 162, 165, 170, 172, 174, 175]. HBV infection was defined in 72% of individual studies as positive by HBV surface antigen test (see Supplemental Table S7 for all definitions).…”
Section: Resultsmentioning
confidence: 99%
“…Congenital defects were slightly higher in children born from mothers who started ARVs in the first trimester (1.7–4.5%) (Watts et al , ; APR, ) compared to those who were exposed only in the second/third trimester (1.2–3.8%) (Patel et al , ; Watts et al , ). Moreover, the results of a 10‐year Italian study showed that ARV drug first‐trimester exposure did not increase the risk of congenital abnormalities (Floridia et al , ). One of the best tools currently available to register child outcomes of ARVs during pregnancy is the Antiretroviral Pregnancy Registry (APR) (APR, ), a prospective exposure‐registration cohort study.…”
Section: Questionsmentioning
confidence: 99%